If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3x = 7x + -11 Reorder the terms: 9 + -3x = -11 + 7x Solving 9 + -3x = -11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + -3x + -7x = -11 + 7x + -7x Combine like terms: -3x + -7x = -10x 9 + -10x = -11 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + -10x = -11 + 0 9 + -10x = -11 Add '-9' to each side of the equation. 9 + -9 + -10x = -11 + -9 Combine like terms: 9 + -9 = 0 0 + -10x = -11 + -9 -10x = -11 + -9 Combine like terms: -11 + -9 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| 52=(3x) | | -22p=-231 | | x^2+4x-40=5 | | 6w-6= | | x^8=36x^6 | | x^2-4x-40=5 | | n+n+2=51 | | -6x+9is=to-21 | | 124=76+32x | | 18x+7=2x | | 334=-7(1-7x)-2 | | x^2+5-30=0 | | v/12=1 | | 52=(3x)+(42x) | | Y+x=325 | | n=687/24(-15) | | x^7=64x^5 | | Y-x=325 | | 3x-8=7-2x | | c/5.3+8.3=11.3 | | m+8=2 | | 2x^2+5=x^2-5x-1 | | 7d=-28 | | 23y=-92 | | -12x+35=0 | | Y=325-x | | 5+2x=65 | | 23y=-28 | | 7x+9-3x=-11 | | x+-5=4 | | 50=1.5x^2 | | 3(5-3z)=0 |